A study of percutaneous injuries amongst health care workers in a tertiary care hospital - Jacob, Aswin Geo; Deodhar, Divya; John, Mary (International Journal of Research in Medical Sciences, 2020)
Background: Percutaneous injuries (PCI) pose a significant risk of occupational transmission of blood borne pathogens to health care workers (HCWs). Their incidence is considerably higher than current estimates, and hence a low injury rate should not be interpreted as a non-existent problem. Methods: This prospective observational study was conducted over a period of 1 year at a tertiary care teaching hospital in northern India. As soon as the HCW sustains a PCI, they were instructed to report to the emergency department where note was made of all the details in the post exposure reporting form. Results: The incidence of PCI in this study was found to be 4.3%. PCIs were reported maximum among nursing staff (63.41%) compared to doctors (36.58%). Majority of PCIs were reported within 1 hour of sustaining the injury (57.1%). Needle stick injury was the commonest injury sustained by HCWs (84.5%). 91.46% of HCWs were fully immunized against hepatitis B. Conclusions: Preventing PCI is an essential part of infection control program in a hospital. Stress must be laid for mandatory reporting of all PCI irrespective of the source.